Implementation of Tahlili, Ijmali and Muqāran Methods in Thematic Hadith Study - Nasution, Zakiah; Partahian; Hasanah, Nur (International Journal of Science and Environment (IJSE), 2026)
The study of the Prophet's hadith encompasses not only the authenticity of sanad and matan but also the methodology of understanding (syarh) employed by Muslim scholars in their commentaries. This study aims to examine the implementation of three hadith commentary methods, namely the tahlili, ijmali, and muqarin methods, and their relevance in the academic development of hadith studies. This research employs a qualitative approach through library research, with data collected from authoritative hadith commentary books and relevant hadith methodology literature. The findings indicate that each of the three methods has distinct characteristics, strengths, and limitations. The tahlili method provides comprehensive and in-depth understanding of each hadith but is susceptible to partial and subjective interpretation. The ijmali method offers concise and accessible explanations, yet is limited in analytical scope. The muqarin method provides broader insights through comparative analysis of hadith texts and scholarly opinions, although it is less suitable for novice readers. This study concludes that the selection of an appropriate commentary method depends on the research objective, the target audience, and the contextual problem under investigation, so that a comprehensive and contextual understanding of hadith can be optimally achieved.